Indicators of active faults on the example of Gomel Structural Bridge - А. Р. Gusev (Известия высших учебных заведений: Геология и разведка, 2024)
Introduction. Modern geodynamic activity manifests itself in fault zones of aseismic regions as fluctuations in the fluid-gas regime, which determines the importance of gas geochemical indicators.Aim. Diagnostics of the modern geodynamic activity of fault zones in the Gomel Structural Bridge based on a set of indicators (thickness of Quaternary deposits, relief, hydrographic network, hydrogen and methane anomalies)/Materials and methods. Studies of the modern activity of fault zones were carried out by indication and geochemical methods (study of subsoil gases and methane content in the troposphere).Results. The relationship between fault zones and the morpholithogenic basis of landscapes was studied. Based on the anomalous thickness of Quaternary deposits and erosion of Paleogene deposits, glacial troughs controlled by fault zones were discovered (in the northern and southwestern parts of the Gomel Structural Bridge). Gas-geochemical anomalies were recorded in the subsurface air and groundwater. The ground gas geochemical anomalies correspond to increased concentrations of tropospheric methane.Conclusion. Gas anomalies indicate a different degree of modern activity of fault zones. The greatest geodynamic activity is typical of the northern part of the Gomel Structural Bridge.